Kandungan Giberelin, Kinetin, dan Asam Absisat pada Tanaman Durian yang Diberi Paklobutrazol dan Etepon - Sakhidin .; Slamet Rohardi Suparto (Indonesian Society for Horticulture / Department of Agronomy and Horticulture, 2011)
Application of paclobutrazol and ethephon is a method to induce flowering of durian. Mecanism of flowering induction was related with the content of some endogenous hormones. The objective of this research was to study content of gibberellin, kinetin, and abscisic acid on durian plant treated by paclobutrazol and ethephon. The treatments were paclobutrazol dosages (a.i. g per tree) : 0,2, and 4; and ethephon concentration (ppm) : 0, 400, and 800; it were replicated 3 times. The material of this research was durian plant var Monthong 10 years age. The result showed that interaction between paclobutrazol dosages and ethephon concentration affected significantly the number of flower and content of gibberellin and abscisic acid. Plant durian treated by 4 g paclobutrazol and 800 ppm ethephon has the lowest content of gibberellin and abscisic acid but the highest number of flower. Application of 4 g paclobutrazol showed the lowest content of gibberellin but the highest content of kinetin. The same result was showed by 800 ppm ethephon.Key words : durian, paclobutrazol, ethephon, edogenous hormones